Universities' and Academics' Resources Shaping Satisfaction and Engagement: An Empirical Investigation of the Higher Education System - Jana Prodanova; Ljupco Kocarev (MDPI AG, 2023)
Higher education research has claimed that the successful future of the educational service is highly dependent on the competencies and observations of the participants in the system, where service quality, employee satisfaction and engagement play an essential role in organizational competitiveness. Therefore, to contribute to the scarce investigation of the role of the institutions' efforts in the support of engaged academics, we aim to assess the quality of higher education from an internal angle by investigating universities' and academics' resources as the antecedents of job satisfaction and engagement. The data from a survey with 322 academics from Macedonian public universities were analyzed using partial least squares structural equations modelling. The results of the estimated model reveal that institutional and educational capacities and academics' adequate competencies are essential for accomplishing favorable perceptions, leading to a committed community dedicated to improving the higher education system. The implications underline that it is vital to recognize the institution's potential by identifying and assessing the resources and capacities it possesses or can access. Moreover, to involve satisfied employees, universities must encourage academics' position and integrity in the institution and promote harmonious collaboration while motivating their capacities and excellence development.